Effectiveness and Safety of Compound Chinese Medicine plus Routine Western Medicine in In-Stent Restenosis: A Meta-Analysis and Systematic Review. (11th July 2018) - Liu, Lu; Liu, Jing; Gao, Qun; Wu, Yang; Lu, Jinjin; Wan, Jie; Li, Yan; Cui, Xiaoyun; Zhou, Kun; Jia, Wenhao; Huang, Yanchao; Qu, Wenbai; et al.
Abstract : Objective. To examine the effects and safety of oral compound Chinese medicine (CCM) plus routine western medicine (RWM) in in-stent restenosis (ISR). Methods. Various electronic databases (CBM, CNKI, VIP, Wanfang, PubMed, EMBASE, and Cochrane Library) were searched until April 2017. The quality of the included studies was evaluated, and meta-analyses were performed using RevMan5.3 and STATA 12.0 software. Moreover, funnel plot and Egger's publication bias plots were analysed to identify publication bias and adverse reactions were reported. A sensitive analysis was carried out according to the quality score. Results. In all, 40 RCTs involving 4536 patients were selected for this review. The pooled estimates of three studies showed that the benefit to the number of ISRs (NoR) was more substantial for CCM plus RWM than for RWM alone (RR 0.24, 95% CI 0.10 to 0.57, P = 0.001 ; I 2 = 0 %, P = 0.81 ). The rate of ISR was significantly lower for CCM plus RWM than for the same RWM alone (RR 0.44, 95% CI 0.37 to 0.53, P < 0.00001 ; I 2 = 0 %, P = 0.95 ). CCM plus RWM benefitted the rate of ISR when a CM placebo plus RWM was used as the control intervention (RR 0.34, 95% CI 0.20 to 0.57, P < 0.0001 ; I 2 = 0 %, P = 0.95 ). The difference of adverse reactions was not significant. For secondary outcomes, the CCM plus RWM group did not reduce the rates of revascularization and cardiac death, but it did reduce the rate of recurrent angina over the results observed in the RWM alone group. In addition, funnel plot and Egger's publication bias plot indicated that there was publication bias. The association between the use of CCM plus RWM and RWM alone remained significant after the sensitivity analysis excluding studies with low quality score (quality score ⩽ 4) with a pooled RR of 0.41 (95% CI, 0.34–0.50). Conclusion. Oral CCM plus RWM clearly benefitted patients with percutaneous coronary intervention (PCI) because it prevented and treated ISR better than was observed for either RWM alone or a CM placebo plus RWM.